Gender inequality in science, technology, engineering and mathematics: gendered time disparities in perceived and actual time spent in practical laboratory-based activities - Fernandez, Daniela; White, Sarah; Smith, Helen C. M.; Connor, Peter M.; Ryan, Michelle (Frontiers in Education, 2023)
In two studies (N = 544) we examined gender differences in the time that students spent, and perceived they spent, on various laboratory-based activities. We predicted that female (vs male) students in STEM would both perceive, and actually spend, less time in practical, science-specific activities, such as using equipment, compared to observing or note-taking. Study 1a (N = 227) was an online, cross-sectional survey where university STEM students reported their perceptions of time spent during lab-based practical activities, and how satisfied they were with their time spent in these activities. Study 1b (N = 318) was an observational study of university practical lab sessions in STEM disciplines. Our findings demonstrated that female (vs male) students (1) spent more time recording and taking notes during lab sessions, (2) did not perceive, yet actually spent, less time in the lab using equipment, and (3) were equally satisfied with their time in the lab using equipment. Together, these results suggest that women occupy stereotypically gendered roles in the STEM lab, spending less time on activities that are key for their professional development. Furthermore, the fact that students from disciplines with more female participation were more satisfied with their time spent in lab activities can promote the insidious effects of assessing gender participation and equality in STEM through numbers only. The differences in time spent in lab activities -yet the lack of acknowledge of these differences-opens the discussion about how women might be receiving reduced utility from their programmes, and that universities may not be delivering on their obligations to ensure equal access to teaching resource and opportunities.the limited research we are able to find suggests observing labs in STEM is critical for two key reasons. First, a lesser interaction with lab equipment could contribute to women perceiving themselves to be incongruent with the role of a Deleted: n